Da'wah Communication of Bedhaya Tunggal Jiwa Dance at Grebeg Besar Ceremony in Demak Regency - Indriana Arninda Dewi; R M Pramutomo (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2019)
Bedhaya Tunggal Jiwa dance is a group dance existing and developing in Demak Regency. It is included in a series of processions at Grebeg Besar religious ceremony in Demak Regency as a guest welcoming dance. Grebeg Besar is a religious ceremony taking place in Demak Regency that is held once a year, precisely on Eid al-Adha. The existence of Bedhaya Tunggal Jiwa dance at Grebeg Besar is one of the media to harmonize culture and religion. The performance contains da’wah elements, so every part of Bedhaya Tunggal Jiwa contains various messages communicated to the public. The overall message focuses on its efforts to remind people to always do good or call for something good for themselves and others. These messages can be identified through movement, makeup fashion, floor pattern, property, and dance music. The method used in this study was qualitative research method with ethnocoreology approach by adopting the concept of form by Suzanne K Langer and the concept of art communication by Santosa. The field study was carried out to obtain objective data carried out through observation, data analysis, and report writing.